L'autorité du corps féminin dans le roman L'Événement d'Annie Ernaux - Maulidia, Kinanti Rahmah; Kurniawati, Novi; Sunahrowi; Yulianto, Ahmad (Universitas Negeri Semarang, 2024)
Annie Ernaux's L'Événement is a novel that depicts the oppression of women by a patriarchal society that considers them “other”, which means they have no control over their bodies. As a result, they have no choice but to control their sexuality and reproduction. Awareness of the oppression suffered by women provokes resistance on the part of female characters to gain authority over their bodies. The aim of this study is to examine the forms of oppression with regard to women's bodily authority and women's struggle to obtain their bodily authority. This research uses a qualitative and feminist approach. The material object of this research is Annie Ernaux's novel L'Événement, and the formal object is women's bodily authority, which is in line with Simone de Beauvoir's concept of existentialist feminism. The results showed that the oppression of women's body authority manifested itself in the form of sexual control, reproductive control and alienation. The conclusion is that, in the novel L'Événement, the female characters suffer oppression of their bodily authority, particularly in matters of sexuality and reproduction, but that the female characters fight against this oppression.